3-T Diffusion tensor imaging of the optic nerve in subjects with glaucoma: correlation with GDx-VCC, HRT-III and Stratus optical coherence tomography findings. Issue 7 (24th May 2012) - Nucci, Carlo; Mancino, Raffaele; Martucci, Alessio; Bolacchi, Francesca; Manenti, Guglielmo; Cedrone, Claudio; Culasso, Franco; Floris, Roberto; Cerulli, Luciano; Garaci, Francesco Giuseppe
Abstract : Objectives: To correlate diffusion-tensor imaging (DTI) of the optic nerve with morphological indices obtained by scanning laser polarimetry (GDx-VCC); confocal scanning laser ophthalmoscopy (Heidelberg III retinal tomograph; HRT-III) and optical coherence tomography (Stratus OCT). Methods: Thirty-six subjects (12 with no eye disease and 24 with perimetrically diagnosed glaucoma) were examined. One eye for each participant was studied with 3-Tesla DTI (with automatic generation of mean diffusivity (MD) and fractional anisotropy (FA) values); GDx-VCC, HRT-III and OCT. Single and multiple regression analyses of all variables studied were performed. Results: MD displayed the strongest correlation with linear cup/disc ratio (LCDR) from HTR-III (r=0.662), retinal nerve fibre layer (RNFL) thickness (avThickn) from OCT (r=−0.644), and nerve fibre index (NFI) from GDx (r=0.642); FA was strongly correlated with the LCDR (r=−0.499). In multiple regression analyses, MD correlated with LCDR (p=0.02) when all variables were considered; with avThickn (p<0.01) (analysis of all RNFL parameters); with NFI (p<0.01) (analysis of all GDx parameters); with avThickn (p<0.01) (analysis of OCT parameters); with LCDR (p=0.01) (analysis of HRT-III morphometric parameters) and with linear discriminant function (RB) (p=0.02) (analysis of HRT-III indices). As for FA, it correlated with avThickn (p=0.02) when we analysed the OCT parameters and with RB (p=0.01) (analysis of HRT-III indices). Conclusions: DTI parameters of the axonal architecture of the optic nerve show good correlation with morphological features of the optic nerve head and RNFL documented with GDx-VCC, HRT-III and OCT.